2017
DOI: 10.3168/jds.2016-12288
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: A reproductive tract scoring system to manage fertility in lactating dairy cows

Abstract: We developed a reproductive tract size and position score (SPS) system as a reproductive management tool to identify lactating dairy cows with decreased fertility. This system, relying solely on transrectal palpation, considers the size (cervical and uterine) and position of the reproductive tract relative to the pelvis. Cows undergoing pre-breeding exams were identified as having reproductive tracts that were small (SPS1), medium (SPS2), or large (SPS3). Cows designated SPS1 had small and compact uterine horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Understanding reproductive failure in cows which have previously been reproductively competent can be specifically challenging. Large reproductive tract size has been associated with decreased fertility in both primiparous and multiparous lactating dairy cows and may be due to sperm transport challenges or increased failure of correct maternal recognition of pregnancy (Baez et al, 2016;Young et al, 2017). The unknown physiological ramifications of increased reproductive tract sizes may persist beyond pregnancy establishment as Madureira et al (2017) reported increased ovulation failure, decreased circulating concentration of PAGs and increased pregnancy loss between day 30 and 120 in cows with the largest reproductive tracts compared to those with decreased tract sizes.…”
Section: Maternal Vs Paternal Contribution To Pregnancy Loss Female Cmentioning
confidence: 99%
“…Understanding reproductive failure in cows which have previously been reproductively competent can be specifically challenging. Large reproductive tract size has been associated with decreased fertility in both primiparous and multiparous lactating dairy cows and may be due to sperm transport challenges or increased failure of correct maternal recognition of pregnancy (Baez et al, 2016;Young et al, 2017). The unknown physiological ramifications of increased reproductive tract sizes may persist beyond pregnancy establishment as Madureira et al (2017) reported increased ovulation failure, decreased circulating concentration of PAGs and increased pregnancy loss between day 30 and 120 in cows with the largest reproductive tracts compared to those with decreased tract sizes.…”
Section: Maternal Vs Paternal Contribution To Pregnancy Loss Female Cmentioning
confidence: 99%
“…The most cows with size and position score of reproductive tract 1 and 2 were clean and pregnant in compare with cows with SPS3 score. Higher rate of pregnancy per artificial insemination was reported for cows were SPS1 than cows were SPS2 or SPS3 ( Young et al., 2017 ). Diameter, volume and length of uterus affect pregnancy rate in cows.…”
Section: Discussionmentioning
confidence: 98%
“…Also, at first examination the cows were divided into three groups according to the size and the position of reproductive system (SPS): cows were diagnosed as having small (SPS1), medium (SPS2), or large reproductive tracts (SPS3). Cows considered SPS1 had small and involuted uterine horns that remained within the pelvic cavity; the reproductive tracts of cows with SPS2 were intermediate in uterine horn and cervical diameter and longer uterine horns leaving partial pelvic cavity; and SPS3 cows had reproductive tracts that were larger and rested mostly outside the pelvic cavity ( Young et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other physiologic traits, such as hormone concentrations, not only require frequent monitoring but are also time-consuming, often invasive in nature, and expensive to quantify, making it difficult to implement in commercial dairy operations. The reproductive tract scoring system first reported in beef cattle has a heritability estimate of 0.32 (Anderson et al, 1991) and is positively associated with pregnancy per AI in beef (Anderson et al, 1991) and dairy cattle (Young et al, 2017;Madureira et al, 2020). The latter trait, however, is subjective, labor-intensive, and has low repeatability (Holm et al, 2009;Gutierrez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%